Spatial distribution and influencing factors of soil available silicon in farmland cultivated layers in Conghua District - QU Yue (Agro-Environmental Protection Institute, Ministry of Agriculture, 2021)
To explore the spatial distribution and influencing factors of available silicon in agricultural soils in Conghua District, Guangzhou City, with a view of providing scientific basis and reference for promoting the growth of rice yield in the main grain-producing areas of China, descriptive statistics, geostatistics, correlation analysis and GIS technology were used to study the soil available silicon in Conghua District. The results showed that the average content of soil available silicon in the study area was 60.31 mg·kg-1, which was generally low and showed moderate variation; in the central area, main grain production areas and hilly areas, the soil available silicon content was relatively high; the effective silicon content was positively correlated with soil pH, organic matter content, and clay content. The land use patterns and soil parent materials also had a significant impact. The study shows that the parent material is the most important among the factors considered.